2015
DOI: 10.15416/ijcp.2015.4.2.77
|View full text |Cite
|
Sign up to set email alerts
|

Association between Perceived Value and Self-Medication with Antibiotics: An Observational Study Based on Health Belief Model Theory

Abstract: Tingginya perilaku swamedikasi antibiotik dapat meningkatkan peluang penggunaan antibiotik yang tidak rasional sehingga berdampak pada peningkatan resistensi antibiotik. Perubahan perilaku swamedikasi antibiotik diperlukan untuk menurunkan penggunaan antibiotik yang irasional. Penelitian ini bertujuan untuk mengetahui hubungan persepsi masyarakat terhadap praktik swamedikasi antibiotik yang bermanfaat untuk mengembangkan model intervensi dalam rangka menurunkan praktik swamedikasi antibiotik (SMA). Studi obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…21 Patients' adherence may be influenced by age, sex, edu cation level, knowledge, and beliefs in antibiotics. 6,15,24,25 Unwise use of antibiotics and incompliance with prescriptions could result in antibiotic resistance. 9 Antibiotic resistance then increases mortality rates, length of hospital stay, and costs of antibiotic therapy and health services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Patients' adherence may be influenced by age, sex, edu cation level, knowledge, and beliefs in antibiotics. 6,15,24,25 Unwise use of antibiotics and incompliance with prescriptions could result in antibiotic resistance. 9 Antibiotic resistance then increases mortality rates, length of hospital stay, and costs of antibiotic therapy and health services.…”
Section: Discussionmentioning
confidence: 99%
“…4 The Health Belief Model (HBM) suggests that a person's health behavior is influenced by factors that can be modified (age, sex, ethnicity, level of education, and knowledge), beliefs, actions triggered by the media, and other factors. 5,6 Previous studies conducted in Lithuania showed that 1,005 adult patients (61% of survey respondents) had low levels of knowledge about antibiotics. 7 A study in Maryland explains that patients' beliefs are shaped through several perceptions, such as perceived severity, perceived susceptibility, perceived benefit, and perceived barriers and cues to action, which in turn affect patients decision making on treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Respondents reported they purchased antibiotics for self-medication at the pharmacy (46-90%), [94][95][96]99,104,106,109,112 at the kiosk (20-44%), 96,104 or received them from family and friends (9-12%). 95,109 20-100% of community respondents reported that they had ever self-medicated with an antibiotic (11), [94][95][96]99,102,104,106,109,[112][113][114] and 87-100% had ever purchased an antibiotic without a prescription…”
Section: Knowledge Attitudes and Perceptions On Antibiotic Use Among ...mentioning
confidence: 99%
“…The existence of factors that influence attitudes will make the formation or change of a person's attitude. 12 According to Insany et al (2015) the experience of the community when doing self-medication using a prescription from a previous doctor greatly affects expectations for the next treatment. 9 Personal experience is one of the factors that can influence the formation of individual attitudes and behavior.…”
Section: Differences In Attitude and Accuracy Of Self-medication Cont...mentioning
confidence: 99%
“…can come from outside himself. 9 The existence of a desire that arises from himself or others will also affect a person in taking action. When someone wants to heal and has the opportunity to get it, someone will try to get it.…”
Section: Introductionmentioning
confidence: 99%